POLEMIK PERLINDUNGAN PENGUNGSI INTERNASIONAL DI TENGAH PANDEMI COVID-19: STUDI KASUS PENGUNGSI ROHINGYA DI COX’S BAZAR - Tiffany Setyo Pratiwi (Dauliyah Journal of Islamic and International Affairs, 2021)
This paper would like to analyze the most vulnerable group that impacted in COVID-19 pandemic, namely refugees. Refugees or forced migrants are the groups that looking for safe places from their home country. Now, there are more than 70 million refugees in the world. This paper would like to explains how COVID-19 gives e ect for refugees in Bangladesh, Rohingya’s refugees in Cox’s Bazar. Second, this paper would like to explains the response of the government to handling this pandemic for refugee’s life and the role of organization that engages to help them. Also, this paper found out that government of Bangladesh try to help Rohingya’s refugees although threat of national security happen.